Fattigdom og den markedsliberale orden. Elementer af færøsk socialhistorie 1767-1855 - Hovgaard, Gestur (Historisk Tidsskrift, 2021)
Poverty and the liberal market order. Elements of Faroese Social History 1767–1856 In the 1850s, the Faroe Islands, a peripheral North Atlantic island community, experienced fundamental institutional changes, of which the introduction of free trade on 1 January 1856 marked the final breakthrough into a modern market society. This article analyses the same general societal change through the lens of the poor-relief system. A public poor-relief law was established in 1767 and revised in 1855. Although the law did not change for nearly 100 years, its practice changed from a system designed to protect the peasant community to a system underpinning the formation of a free market. This is seen by the attempts of the administrative elite to transform common people from peasants into workers, e.g. by sending them on board fishing vessels or by giving the poorest inhabitants of the main city, Torshavn, loans in order to establish them as coastal fishermen. For these reasons, the period before 1856 is not as static as is often believed. Although delayed, general (European) ideas of modernization merged with traditional Faroese community structures in local institutional arrangements. For example, no workhouse was ever established. Instead, public support was provided to house the homeless in traditional farmhouses. While enlightened Danish officials were the driving force of early Faroese modernization, the Faroese peasant elite, and even the poor themselves, learned to adapt and influence new institutional practices. Hence, early Faroese modernization was a politically initiated and planned process in which the poor population was considered both a problem and an opportunity in shaping the future liberal order.